2021
DOI: 10.3390/en14092394
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on Electricity Consumption and Economic Growth in Romania

Abstract: This paper analyzes the impact of the COVID-19 pandemic on economic growth and electricity consumption and investigates the hypothesis of the influence of this consumption on the gross domestic product (GDP) for Romania. Using time series on monthly electricity consumption and quarterly GDP and a multi-linear regression model, we performed an analysis of the evolution of these indicators for 2007–2020, a comparison between their behavior during the financial crisis vs. COVID-19 crisis, and empirically explore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 59 publications
4
17
0
Order By: Relevance
“…Analogous results were observed in the province of Ontario in Canada, where a reduction in the overall electricity demand of 14% was observed in April 2020, as well as a flattening of the load demand, especially during peak hours ( Abu-Rayash and Dincer, 2020 ). A similar trend has been reported for South Asia ( Lowder and Leisch, 2020 ) and Romania ( Soava, Mehedintu, Sterpu and Grecu, 2021 ). Analyzing the types of users independently, the residential electricity demand increased, showing a shift and change in the shape of the load profiles, while the electricity in the commercial and industrial sectors decreased.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…Analogous results were observed in the province of Ontario in Canada, where a reduction in the overall electricity demand of 14% was observed in April 2020, as well as a flattening of the load demand, especially during peak hours ( Abu-Rayash and Dincer, 2020 ). A similar trend has been reported for South Asia ( Lowder and Leisch, 2020 ) and Romania ( Soava, Mehedintu, Sterpu and Grecu, 2021 ). Analyzing the types of users independently, the residential electricity demand increased, showing a shift and change in the shape of the load profiles, while the electricity in the commercial and industrial sectors decreased.…”
Section: Introductionsupporting
confidence: 87%
“… Energy simulation Energy use Users Case study Main findings ( Ghiani, Galici, Mureddu and Pilo, 2020 ) Real measured data Electricity All the users Italy A reduction in the electricity consumption of up to 37% was observed during the full lockdown period, ( Liu and Lin, 2021 ) Machine learning model Electricity All the users The UK A reduction in the overall electricity consumption was observed during the lockdown period ( Madurai Elavarasan et al, 2020 ) Real measured data Electricity Residential, commercial, industrial users India A significant increase in the residential electricity demand and a reduction in industrial and commercial consumption were observed during the lockdown period ( Abu-Rayash and Dincer, 2020 ) Real measured data Electricity All the users Ontario, Canada The overall electricity demand for the Ontario province decreased by 14% in April 2020 during the lockdown. ( Lowder and Leisch, 2020 ) Real measured data Electricity Residential, commercial, industrial users South Asia An increase in the residential electricity consumption and a reduction in the commercial and industrial usage were observed during the lockdown and this led to a shift and change in the shape of the load profiles ( Soava, Mehedintu, Sterpu and Grecu, 2021 ) Real measured data Electricity Residential, commercial, industrial users Romania An increase in the residential electricity consumption and a reduction in non-residential electricity consumption were observed during the lockdown. ( Geraldi et al, 2021 ) Real measured data Electricity Municipal users Florianópolis, Brazil A reduction in the electricity consumption of municipal buildings was observed during the lockdown: 11.1% in health centers, 38.6 % in administrative buildings, 50.3 % in elementary schools, and 50.4% in nursery schools.…”
Section: Introductionmentioning
confidence: 99%
“…This increase was proportional to the number of people in the family whose daily existence was limited to functioning in the place of residence. The increase in the cost of electricity consumption is also confirmed by the results of research carried out around the world, including Poland [44][45][46]. It should be noted that each of the reports indicates a decrease in consumption in the national dimension, with a simultaneous increase in consumption in the household dimension.…”
supporting
confidence: 52%
“…Other studies sought to examine the impact of the pandemic on economic growth and energy consumption. In order identify the relationship between gross domestic product and electricity consumption in Romania, Soava et al [100] used a linear regression model. The significant impact of commercial energy consumption on gross domestic product in the pandemic was determined.…”
Section: Impact On Consumption and Habitsmentioning
confidence: 99%